Oil Spill Exposure and Environmental Health Risks: A Guidance and Counselling Framework for Promoting Environment Sustainability in the Niger Delta - Nathan Udoinyang; Wobodo Brighten CHINWEATU (RADINKA JOURNAL OF HEALTH SCIENCE, 2026)
This study examines oil spill exposure and environmental health risks in the Nigerian Niger Delta and proposes a guidance and counseling framework for promoting environmental sustainability. The study adopts a mixed-methods approach, combining quantitative surveys and qualitative interviews across selected states and local government areas. A total of 600 respondents, including farmers, fishermen, traders, and civil servants, participated in the study. Descriptive analysis revealed high levels of oil spill exposure and environmental health risks, alongside moderate environmental awareness. Regression analysis showed a significant positive relationship between oil spill exposure and health risks, as well as between environmental awareness and sustainable behavior. Thematic analysis further identified key issues such as health concerns, economic losses, psychological stress, low awareness, and institutional distrust. The findings highlight the multidimensional impacts of environmental degradation and the limitations of existing technical interventions. The study concludes that guidance and counseling frameworks can play a critical role in enhancing environmental awareness, promoting behavioral change, and improving community resilience. It recommends the integration of counseling programs into environmental policies, increased public education, and stronger institutional accountability to achieve sustainable development in the Niger Delta.